Sungai sebagai sumber kehidupan: pencemaran tehadap ancaman keberlangsungan hidup masyarakat - Nofrizal Nofrizal; Thamrin Thamrin; Zulfan Sa’am; Tengku Said Raza’i; Ramses Ramses (CANANG: Jurnal Pengabdian Masyarakat, 2021)
A series of counseling and discussion activities with the community in Kampung Baru Sentajo, Sentajo Raya District, Kuantan Singingi Regency were carried out with the purpose to increase knowledge, understanding of environmental sustainability and community empowerment towards efforts to prevent river pollution by community activities themselves. This counseling activity was attended by 30 participants with occupational backgrounds such as teachers, civil servants, farmers, journalists, housewives, and fishermen. Meanwhile, their education level starts from elementary school level to bachelor degree. Analysis of measuring activity achievement used descriptive analysis and descriptive statistical calculations. The descriptive statistical calculation uses the ratio of participants to items taken with the total extension participants who attend as a community in Kampung Baru Sentajo, Kuantan Singingi Regency. The analysis results are presented in the form of a pie graph. The results of the evaluation of the activities showed that 89.9% of the people represented by the counseling participants who attended stated that the existence of rivers is very important for life. Meanwhile, another 11.1%, the existence of the river is important for themselves and for the livelihood of many people. As many as 66.7% of them realized that the river in their environment had changed greatly and 33.3% the condition of the river had changed. As much as 55.6% of all participants who attended this counseling activity, the material presented were useful. While 38.9% is very useful. The interesting thing was that there were 5.6% who stated that extension activities were useless. Even though there were 5.6% of participants who took part in the counseling activities provided were useless, all participants of the event had interesting (50%) and very interesting (50%) content. The hope of the participants is that this counseling can be carried out in every village in Kuantan Singingi Regency, especially in villages that are central to unlicensed gold mining (PETI) by involving all village officials. In addition, the participants also expect to get material on practical ways to reduce pollution by liquid waste.